Developing a spiritual care model for patients and their relatives in illness - Marta Georgina Oliveira de Góes; Maria da Graça de Oliveira Crossetti (Universidade Federal do Rio Grande do Sul, 2020)
ABSTRACT Objective: To develop a spiritual care model for patients and their relatives in illness. Methodology: A qualitative study that uses Symbolic Interactionism as theoretical framework, and the Grounded Theory designed by Charmaz as methodological framework. Semi-structured interviews were performed with 10 participants, and the Model was validated by an expertise group, from march to may 2016, at a University Hospital in the South of Brazil. When analyzing the data, the following codifications were made: initial, focalized, axial and theoretical. Results: The categories that structured the Model were the following: Situating spirituality in their daily lives; Exercising spirituality in life; Perceiving the role of the nursing team in spiritual care; Identifying the manifestations of spiritual needs; Placing spirituality as a priority in care and Re- signifying the illness process. Conclusion: Developing the model has enabled us to achieve a conceptual understanding and interpretation of spiritual care in nursing and to draw up the connections among the nursing team, the patients and their relatives.